Structural Unemployement in Canada: 1971-1974. Did It Worsen? - Cousineau, Jean-Michel; Green, Chris (Relations industrielles / Industrial Relations, 1978)
The paper examines the question whether « structural » unemployment in Canada worsened during the period 1971-1974. Structural unemployment is here defined as a mis-match between the location and skill of job seekers and the location and skill requirements of available jobs (vacancies).